Analisis Analisis Peran Dinas Perindustrian Perdagangan Koperasi dan UKM dalam Pengembangan Industri Tenun Sutera di Kabupaten Wajo - Amrizal Akmul Amrizal; Deddy T. Tikson; Hasniati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2026)
This study was motivated by the continuing need for support and intervention from the local government, particularly the Department of Industry, Trade, Cooperatives and SMEs, in developing the silk industry as one of the leading creative economic sectors in Wajo Regency. Pakkanna Village, as one of the centres of silk craftsmanship, faces various challenges in maintaining its existence, in terms of human resources, technology and marketing. This study aims to determine the role of the government in supporting the sustainability and growth of the silk industry. This study uses a qualitative method with a descriptive approach. The research subjects consist of the Head of the Office, the Head of the Industry Division, and several silk weavers. The data collection techniques used consist of interviews, observation, and documentation. The results of the study show that the government has an important role in education, training, guidance, and promotion. In addition, there are inhibiting factors such as low interest among the younger generation in weaving businesses, limited access to capital, and weak artisan institutions. Based on the results of the study, it is concluded that active government involvement greatly influences the success of developing the silk weaving industry as part of community economic empowerment.